Study of Epitope Imprinting for Small Templates: Preparation of NanoMIPs for Ochratoxin A. Issue 5 (14th March 2019) - López‐Puertollano, Daniel; Cowen, Todd; García‐Cruz, Álvaro; Piletska, Elena; Abad‐Somovilla, Antonio; Abad‐Fuentes, Antonio; Piletsky, Sergey
Abstract: Ochratoxin A (OTA) is a carcinogenic mycotoxin produced by Aspergillus and Penicillium, which contaminates cereals like corn and wheat, in addition to beverages such as coffee, wine and beer. Chromatography is the preferred analytical method for OTA determination, but unfortunately this method is still elaborate, expensive and tedious. Alternative mycotoxin detection techniques involve assays and sensors based on molecularly imprinted polymers nanoparticles (nanoMIPs) as synthetic polymeric receptors mimicking antibodies. Herein we designed nanoMIPs for specific recognition of OTA using computational screening and docking of different acryl functional monomers. Subsequently, different nanoMIPs were prepared by solid phase synthesis using two OTA haptens, OTA e‐ MIPs without carboxylic group and OTA b‐ MIPs bearing the carboxylic group. NanoMIPs affinity towards OTA was analyzed by surface plasmon resonance, the results displayed dissociation constants for OTA b‐ MIPs at 0.4  μM and for OTA e‐ MIPs at 5.1  μM. Therefore, the results demonstrate that nanoMIPs recognition depends on the immobilization position of the OTA hapten as observed using antibodies. Abstract : Imitating with imprinting : The importance of the spatial availability of the template functional groups is shown during the synthesis of molecularly imprinted nanoparticles.